When school-based, in-service teacher training sharpens pedagogical awareness. (March 2020) - Lund, Lea
Research in the field of professional development (PD) stresses the importance of the development of professional learning communities (PLCs) designed to promote the process of inquiry in teaching. PLCs are of great importance with regard to both school improvement and in-service teacher training. This article shows that it is possible to teach teachers to reflect on their beliefs and actions, making them visible to teachers and their colleagues during a cooperative process of inquiry in the classroom. The empirical data stem from a 2-year, school-based, in-service teacher-training program involving 16 teachers at two Danish high schools. The research question is 'how can teachers' reflections, pedagogical awareness, and perspectives on their beliefs be sharpened by in-service teacher training?' With regard to school improvement, two conclusions are drawn: (1) teachers' pedagogical awareness is sharpened and their classroom behavior and educational thinking change when their routine actions and thinking are questioned and scrutinized; (2) teachers who experiment systematically with their own teaching alongside their colleagues find the process and product rewarding.